The Balloon Lidar Experiment BOLIDE - Kaifler, Bernd; Kaifler, Natalie; Rempel, Dimitry; Rossi, Philipp; Büdenbender, Hans Christian; Baturkin, Volodymyr (2019)
The Balloon Lidar Experiment BOLIDE was the first mesospheric lidar system carried by a long duration balloon. As part of NASA’s PMC-Turbo balloon payload, the lidar was launched from Kiruna, Sweden in July 2018 on a six day mission to northern Canada. The BOLIDE instrument was primarily designed for high resolution profiling and altimetry of noctilucent clouds, but also provided temperature profiles from 45 km to about 85 km altitude. We discuss the technological challenges and constraints associated with the successful operation of a high-power lidar system on a balloon platform. Although the basic working principle is the same as of any ground-based mesospheric lidar system, BOLIDE faced several requirements unique to a balloon platform. Not only had the instrument to withstand the near-space environment which is characterized by low atmospheric pressure and dominating radiative heating and cooling, but it also had to meet the space, weight and power requirements imposed by the design of the PMC-Turbo gondola. Key features are a compact and robust laser design, a single-loop liquid cooling system involving a high-performance radiator for dumping of waste heat, a thermal protection system, integrated electronics, and a flight computer for command & data handling and data storage. Finally, we compare the in-flight performance of both the lidar and the thermal control system to pre-flight simulations. First scientific results based on BOLIDE measurements will be presented in a second paper.